PERLINDUNGAN HUKUM PEMEGANG HAK ATAS TANAH TERHADAP PERBUATAN MELAWAN HUKUM TERBITNYA SERTIFIKAT GANDA - Limbong, Hansen Alfian; Atmadja, Dhody.AR.Widjaja; Ismed, Mohamad (SINERGI : Jurnal Riset Ilmiah, 2024)
The guarantee of legal certainty regarding land rights has been regulated in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles (UUPA). Especially in Article 19 of the UUPA in ensuring legal certainty, the Government holds land registration throughout Indonesia and the issuance of proof of land rights, namely Certificates. In reality, disputes or legal cases often arise over the issuance of double certificates on the same land plot issued by the local Land Office which results in losses for land rights holders. The formulation of the problem in this study is how the civil responsibility of the land office for the double certificate dispute and how to protect the legal protection of the land right holder for the double certificate dispute. The type of research used in this study is normative juridical with a legislative, conceptual, and case approach. The source of legal materials in this study is secondary data consisting of primary, secondary, and tertiary legal materials using the technique of collecting legal materials, namely literature studies.  The result of this study is the civil responsibility of the land office for court decisions that have permanent legal force for dual certificate disputes, namely recording and/or changing the recording of certificates that are declared valid and/or do not have legal force. There is no compensation in material form from the Land Office to the holder of land rights whose certificate has been declared valid by a court decision that has permanent legal force. Legal protection of land rights holders in a dispute over multiple certificates can be carried out by canceling one of the certificates made by the authorized Head of the Land Office and/or the aggrieved party files a civil lawsuit on the basis of unlawful acts through the competent district court in accordance with the applicable legal provisions.